The Role of Human Resource Management in Managing People risk in Bank - Guo, Litong (2013)
Regulators and risk managers focus primarily on more tangible risks area, such as operational risk, credit risk and market risk. Recently, people risk has increased rapidly in financial service, especially for banks. And it has received a lot of attention by HR managers, because people risk often represent the operational risk linked to HR management.